(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The research aims to study the effect of population momentum and temperatures on the proportion of elements in the soil, as multiple mediation models were applied with regression models to study and indicate the effect of the variables under study. Those samples were laboratory to know the proportions of the effect. A group of elements were studied, including (Na, Mg, K, CI, Ca), and after collecting and tabulating the data, the data was analyzed using the statistical program (R Program) .